2023
DOI: 10.1128/spectrum.01175-23
|View full text |Cite
|
Sign up to set email alerts
|

Tezacaftor/Ivacaftor therapy has negligible effects on the cystic fibrosis gut microbiome

Ryan Marsh,
Claudio Dos Santos,
Liam Hanson
et al.

Abstract: People with cystic fibrosis (pwCF) experience a range of persistent gastrointestinal symptoms throughout life. There is evidence indicating interaction between the microbiota and gut pathophysiology in CF. However, there is a paucity of knowledge on the potential effects of CF transmembrane conductance regulator (CFTR) modulator therapies on the gut microbiome. In a pilot study, we investigated the impact of Tezacaftor/Ivacaftor dual combination CFTR modulator therapy on the gut microbiota and metabolomic func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…With respect to microbiota diversity, we demonstrate a significant shift in the core taxa of pwCF following extended ETI therapy, which translated into a positive trajectory of whole microbiota diversity by the end of the study period. Despite this, diversity was not significantly different following ETI, as shown previously with less efficacious CFTR modulator treatments encompassing shorter administration periods [1517,19]. Interestingly, Kristensen et al did observe significant increases in faecal microbiota diversity [18], but only following extended (12 month) Ivacaftor therapy in a group of pwCF harbouring the S1251N mutation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…With respect to microbiota diversity, we demonstrate a significant shift in the core taxa of pwCF following extended ETI therapy, which translated into a positive trajectory of whole microbiota diversity by the end of the study period. Despite this, diversity was not significantly different following ETI, as shown previously with less efficacious CFTR modulator treatments encompassing shorter administration periods [1517,19]. Interestingly, Kristensen et al did observe significant increases in faecal microbiota diversity [18], but only following extended (12 month) Ivacaftor therapy in a group of pwCF harbouring the S1251N mutation.…”
Section: Discussionmentioning
confidence: 65%
“…Results for the frequently observed inflammation in the gut following modulator treatment are also contrasting. Some studies observed a reduction in faecal calprotectin following modulator usage [15,20,21], whilst others [16] and our own group [19], did not measure any notable reduction.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…These suboptimal strategies to improve CF-associated intestinal disease are now being successfully replaced by CFTR targeted therapy which improves not only the pulmonary but also the intestinal symptoms [ 54 , 88 , 112 ]. Preliminary results suggest that this improvement is not reached via an alteration of the dysbiotic gut microbiota seen in patients with CF [ 108 ]. Recent studies in CFTR null mice aimed to explore strategies to increase the alkalinity and fluidity in an intestine that expressed no functional CFTR protein at all and therefore is not a candidate for CFTR-targeted therapy.…”
Section: Strategies To Influence Luminal Alkalinity In Patients With ...mentioning
confidence: 99%